Risk for surgical positioning injuries: scale validation in a rehabilitation hospital - Francisca Caroline Lopes do Nascimento; Maria Cristina Soares Rodrigues
Objective: to validate the Risk Assessment Scale for the Development of Injuries due to Surgical Positioning in the stratification of risk for injury development in perioperative patients at a rehabilitation hospital. Method: analytical, longitudinal and quantitative study. An instrument and the scale were used in the three perioperative phases in 106 patients. The data were analyzed using descriptive and inferential statistics. Results: most patients showed high risk for perioperative injuries, both in the scale score with estimated time and in the real-time score, with a mean of 19.97 (±3.02) and 19.96 (±3.12), respectively. Most participants did not show skin lesions (87.8%) or pain (92.5%). Inferential analysis enabled us to assert that the scale scores are associated with the appearance of injuries resulting from positioning, therefore, it can adequately predict that low-risk patients are unlikely to have injuries and those at high risk are more likely to develop injuries. Conclusion: the scale validation is shown by the association of scores with the appearance of injuries, therefore, it is a valid and useful tool, and it can guide the clinical practice of perioperative nurses in rehabilitation hospitals in order to reduce risk for injuries due to surgical positioning.